2013
DOI: 10.1016/s0924-9338(13)76898-6
|View full text |Cite
|
Sign up to set email alerts
|

1958 – Efficacy of modified compliance therapy for schizophrenia patients

Abstract: BackgroundSchizophrenia requires a large share of medical resources due to its early onset and chronic and severe nature. Compliance therapy is a therapy specifically designed to improve concordance with treatment for those with major mental illnesses. The aim of present study was to determine whether compliance therapy improves drug adherence and consequently makes better global functioning and improves quality of life in schizophrenic patients.MethodsThis randomized controlled clinical trial study was done i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Such findings supported the positive effect of medication adherence on suppressing depressive symptoms among patients with MDD, which is the core aim of prescribing the antidepressant. The finding supported by RCT studies, patients who received AT reported significant improvements in symptom severity over time (over 6 months and 18 months follow-up) compared with TAU in patients with SSD (Chien et al 2015(Chien et al , 2016Omranifard et al 2013). On the other hand, it is not consistent with studies that found that AT did not significantly improve psychiatric symptomatology than the control group (Anderson et al 2010;Gray et al 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Such findings supported the positive effect of medication adherence on suppressing depressive symptoms among patients with MDD, which is the core aim of prescribing the antidepressant. The finding supported by RCT studies, patients who received AT reported significant improvements in symptom severity over time (over 6 months and 18 months follow-up) compared with TAU in patients with SSD (Chien et al 2015(Chien et al , 2016Omranifard et al 2013). On the other hand, it is not consistent with studies that found that AT did not significantly improve psychiatric symptomatology than the control group (Anderson et al 2010;Gray et al 2006).…”
Section: Discussionmentioning
confidence: 81%
“…The summary ES (Hedges’s g ) across all primary study MI-based CAT intervention and control comparisons was .45 (95% CI [0.139, 0.750]; Z = 2.851, p = .004) in the .20 to .50 range to be considered moderate (Borenstein et al, 2009). Although the summary ES of this meta-analytic study is considered moderate, only six primary studies (Figure 2) had significant ESs (Anderson et al, 2010; Chien et al, 2015; Gray et al, 2004; Maneesakorn et al, 2007; Omranifard et al, 2012; Schulz et al, 2013). Most studies tended toward positive effects though they were not statistically significant.…”
Section: Resultsmentioning
confidence: 89%
“…As a result of the winnowing process (Figure 1), 16 studies were deemed eligible as primary studies for this meta-analytic study. They are identified by asterisks in the reference list (Anderson et al, 2010; Barkhof et al, 2013; Cavezza, Aurora, & Ogloff, 2013; Chien et al, 2015; Gray et al, 2006; Gray, Wykes, Edmonds, Leese, & Gournay, 2004; Hayward et al, 1995; Interian et al, 2013; Kemp et al, 1998; Maneesakorn et al, 2007; O’Donnell et al, 2003; Omranifard, Karahmadi, Jannesari, & Maracy, 2012; Schulz et al, 2013; Staring et al, 2010; Tsang & Wong, 2005; von Bormann, Robson, & Gray, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…10 Poor adherence to antipsychotic medication in schizophrenia have been associated with rehospitalisation and relapse in cross sectional studies and studies monitoring hospital admissions among patients being in shortage of supplies of antipsychotic medications. 12 Data from study revealed that 74 % of the patients discontinued their medication before 18 months, i.e. either to nonadherence or to another antipsychotic medication.…”
Section: Introductionmentioning
confidence: 99%
“…6,16 Patients with mental illness who are non-adherent also are at risk for homelessness, incarceration, and violence. 7,12 Poor adherence can be responsible for avoidable hospital admissions and increased visits to the emergency department. 2 Thus, since adherence is determined to a large extent by one's income, it means non-adherence in a significant proportion of the subjects might be accounted for by these economic considerations.…”
Section: Introductionmentioning
confidence: 99%